New Pregnane Glycosides from Gymnema sylvestre - Rui Xu; Yu Yang; Yang Zhang; Fengxia Ren; Jinlong Xu; Nengjiang Yu; Yimin Zhao (Molecules, 2015)
Four new pregnane glycosides 1–4 were isolated from the ethanol extract of the stem of Gymnema sylvestre and named gymsylvestrosides A–D. Hydrolysis of compound 1 under the catalysis of Aspergilus niger β-glucosidase afforded compound 5 (gymsylvestroside E). Their structures were determined by spectroscopic methods such as HRESIMS, 1D and 2D NMR, as well as HMQC-TOCSY experiment. Compounds 1–4 were screened for Saccharomyces cerevisiae α-glucosidase inhibitory activity.